2016
DOI: 10.1002/pssa.201600297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen impurities in semipolar III‐nitride light emitting diodes

Abstract: We investigate the effect of oxygen impurities on the internal quantum efficiency of semipolar III‐nitride light emitting diodes (LED) structures grown along the false(202‾1false) direction by means of carrier transport simulations. For the model calculations, realistic doping and impurity profiles obtained by secondary ion mass spectroscopy are used. We discuss the impact of the oxygen impurity density on the operation of the LED and the interaction of the donor‐type oxygen impurities with the acceptor doping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Although the presence of O impurity incorporated in p-AlGaN HSL structures might be considered as an unwanted impurity because it acts as a donor in GaN, it was also reported that both 'Mg impurity' and 'O impurity' co-doping may noticeably improve the free hole concentration and mobility in the p-AlGaN films [55][56][57]. The origin of such observations is not yet acceptable, since a direct electronic interaction of the 'O donors' and 'Mg acceptors' is unlikely because the energetic distance between the impurity levels is quite high (43 eV) [58]. Furthermore, the explanation by Katayama-Yoshida and co-workers for this unexpected behavior can also be reasoned [57].…”
Section: Sims Measurement Of the As-grown Led-v25c And The Influence ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the presence of O impurity incorporated in p-AlGaN HSL structures might be considered as an unwanted impurity because it acts as a donor in GaN, it was also reported that both 'Mg impurity' and 'O impurity' co-doping may noticeably improve the free hole concentration and mobility in the p-AlGaN films [55][56][57]. The origin of such observations is not yet acceptable, since a direct electronic interaction of the 'O donors' and 'Mg acceptors' is unlikely because the energetic distance between the impurity levels is quite high (43 eV) [58]. Furthermore, the explanation by Katayama-Yoshida and co-workers for this unexpected behavior can also be reasoned [57].…”
Section: Sims Measurement Of the As-grown Led-v25c And The Influence ...mentioning
confidence: 99%
“…V Ga -O N -H [27], and such complexes were computationally and experimentally associated with charged point defects [45,46]. However, the O impurity concentration needs to be controlled, because it was shown that up to a certain level (10 18 cm 3 ) can be tolerated to maintain a UVB LED device performance [58]. Therefore, the LP-MOVPE gas precursor's sources and reactor assembly should be tightly sealed enough from air to avoid the incorporation of too many residual impurities while growing ternary Al-containing compounds, because otherwise reactions between the TMAl precursor and 'O impurity' in the gas stream may lead to the formation of volatile intermediate products that are potentially responsible for the incorporation of oxygen and other unknown byproducts.…”
Section: Sims Measurement Of the As-grown Led-v25c And The Influence ...mentioning
confidence: 99%